Maximizing the value of consulting : a guide for internal and external consultants - Phillips, Jack J., 1945-; Trotter, William Dow.; Phillips, Patricia Pulliam (Hoboken : Wiley, 2015)
"Provide organized, efficient, relevant consulting with lasting value Maximizing the Value of Consulting is an indispensable, practical guide for managing, measuring, and delivering the results that make internal and external consulting a lasting value to clients and the company. Sponsored by the ROI Institute and the Association of Internal Management Consultants, this book provides a roadmap to relevance for consultants operating in the increasingly fast-paced, changing, dynamic environment. Readers will learn how to use resources properly and manage the investment efficiently, while truly connecting to the business, securing appropriate levels of commitment, and providing adequate levels of support. Detailed coverage includes guidance toward calculating the value of consulting in terms that executives understand, including business impact and ROI, and using the appropriate tools to show how things are working throughout the process. Whether organizations are using internal or external consultants, or both, consultants can provide better value to the company. Consultants are needed to provide advice, support, and insight into the processes undertaken to improve the business, and integrate the input of different functional units into a more streamlined strategy. This book is designed to help consultants provide the utmost value to clients by maximizing organization, efficiency, and ultimately, ROI. Manage for value with better organization and cost control Set objectives at multiple levels to deliver useful results Measure implementation, impact, ROI, and intangibles Use final results to drive appropriate actions, creating lasting value The skyrocketing need for internal and external consultants will continue, in almost every functional area ranging from HR and technology, to auditing and risk management. Maximizing the Value of Consulting provides a manual for relevant, value-driven consulting, with world-renowned expert insight"--
ROI Planning MeetingFinal Thoughts; Chapter 10: Methods of Data Collection; Using Questionnaires and Surveys; Using Interviews; Using Focus Groups; Measuring with Tests; Measuring with Simulation; Using Observation; Using Action Plans; Using Performance Contracts; Monitoring Business Performance Data; Selecting the Appropriate Method for Each Level; Final Thoughts; Chapter 11: Data Collection at All Four Levels; Sources of Data; The Importance of Measuring Inputs, Level 0; Importance of Measuring Reaction, Level 1; The Importance of Measuring Learning, Level 2
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Consultants; Consulting firms -- Management; BUSINESS & ECONOMICS -- Training; Consultants; Consulting firms -- Management; Electronic books